The failure of risk management : why it's broken and how to fix it - Hubbard, Douglas W. (Hoboken, N.J. : Wiley, 2009)
The book explains which risk analysis method work, which don't, and how to tell the difference. The book further discusses topics relevant to the management of risk including: Financial Risks, Natural Disasters, Industrial Accidents, Product Safety, Technology Risks, Project Failures, Engineering Disasters, Pandemic Viruses, Computer Security, Fraud, Loss of Reputation, and Litigation.
Includes bibliographical references and index.
rpm 30/05/13;nmn24/07/13
Loans
Keywords: Risk management